Workplace violence targeting student nurses in the clinical areas - Hewett, Deirdre (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MCur (Interdisciplinary Health Sciences. Nursing Science))--University of Stellenbosch, 2010.